2023
DOI: 10.1002/2211-5463.13558
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish and medaka T1R (taste receptor type 1) proteins mediate highly sensitive recognition of l‐proline

Abstract: In vertebrates, nutritional tastants, such as amino acids and sugars, are recognized by G‐protein‐coupled receptors of the taste receptor type 1 (T1R) family. Previous studies have shown that fish T1Rs are functionally distinct from mammalian T1Rs in certain regards. Here, we report the existence of oral receptors with high sensitivity to amino acids in zebrafish and medaka fish. We describe the construction of multiple cell lines stably expressing functional T1Rs (from medaka fish or zebrafish) with a chimeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…In our previous study, mfT1R2c/mfT1R3 and zfT1R2a/zfT1R3 were identified as highly sensitive receptors for L-Pro 34 . In this study, their EC 50 values for L-Pro were lower in 10 mM Cl − buffer than in high Cl − buffer (Fig.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…In our previous study, mfT1R2c/mfT1R3 and zfT1R2a/zfT1R3 were identified as highly sensitive receptors for L-Pro 34 . In this study, their EC 50 values for L-Pro were lower in 10 mM Cl − buffer than in high Cl − buffer (Fig.…”
Section: Discussionmentioning
confidence: 88%
“…It should be noted that although the fish T1Rs commonly respond to L-amino acids, there are differences in their ligand profiles. While mfT1R2a/mfT1R3 and mfT1R2b/mfT1R3 are broadly tuned receptors, mfT1R2c/mfT1R3 is a narrowly tuned receptor highly sensitive and specific to L-Pro 6 , 8 , 34 . Both zfT1R2a/zfT1R3 and zfT1R2b/zfT1R3 respond to several L-amino acids, though the sensitivity of zfT1R2a/zfT1R3 is higher than zfT1R2b/zfT1R3 6 , 34 .…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Another exception is medaka T1r2c, which contains an alanine at the same residue. This may be related to the fact that medakaT1r2c/T1r3 specifically responds to L-proline, a secondary amino acid, but not to other L-amino acids with a primary amino group [5,28]. Conversely, hummingbird T1r1 and gecko T1r2 share "SSO" residues, whereas hummingbird T1r1/T1r3 and gecko T1r2/T1r3 exhibit sugar responses [26,27].…”
Section: Plos Onementioning
confidence: 99%